The Ethics of Organ Donor Registration Policies: Nudges and Respect for Autonomy. Issue 11 (1st November 2016) - MacKay, Douglas; Robinson, Alexandra
Abstract : Governments must determine the legal procedures by which their residents are registered, or can register, as organ donors. Provided that governments recognize that people have a right to determine what happens to their organs after they die, there are four feasible options to choose from: opt-in, opt-out, mandated active choice, and voluntary active choice. We investigate the ethics of these policies' use of nudges to affect organ donor registration rates. We argue that the use of nudges in this context is morally problematic. It is disrespectful of people's autonomy to take advantage of their cognitive biases since doing so involves bypassing, not engaging, their rational capacities. We conclude that while mandated active choice policies are not problem free—they are coercive, after all—voluntary active choice, opt-in, and opt-out policies are potentially less respectful of people's autonomy since their use of nudges could significantly affect people's decision making.